Integrating strategies of metabolomics, network pharmacology, and experiment validation to investigate the processing mechanism of Epimedium fried with suet oil to warm kidney and enhance yang - Sun, E.; Huang, Ran; Ding, Ke; Wang, Ling; Hou, Jian; Tan, Xiaobin; Wei, Yingjie; Feng, Liang; Jia, Xiaobin (Frontiers in Pharmacology, 2023)
Epimedium, a traditional Chinese medicine (TCM) commonly used in ancient and modern China, is one of the traditional Chinese medicines clinically used to treat kidney-yang deficiency syndrome (KYDS). There are differences in the efficacy of Epimedium before and after processing, and the effect of warming the kidney and enhancing yang is significantly enhanced after heating with suet oil. However, the active compounds, corresponding targets, metabolic pathways, and synergistic mechanism of frying Epimedium in suet oil to promote yang, remain unclear. Herein, a strategy based on comprehensive GC-TOF/MS metabolomics and network pharmacology analysis was used to construct an "active compounds-targets-metabolic pathways" network to identify the active compounds, targets and metabolic pathways involved. Subsequently, the targets in kidney tissue were further validated by real-time quantitative polymerase chain reaction (RT-qPCR). Histopathological analysis with physical and biochemical parameters were performed. Fifteen biomarkers from urine and plasma, involving five known metabolic pathways related to kidney-yang deficiency were screened. The network pharmacology results showed 37 active compounds (13 from Epimedium and 24 from suet oil), 159 targets, and 267 pathways with significant correlation. Importantly, integrated metabolomics and network pharmacologic analysis revealed 13 active compounds (nine from Epimedium and four from suet oil), 7 corresponding targets (ALDH2, ARG2, GSTA3, GSTM1, GSTM2, HPGDS, and NOS2), two metabolic pathways (glutathione metabolism, arginine and proline metabolism), and two biomarkers (Ornithine and 5-Oxoproline) associated with improved kidney yang deficiency by Epimedium fried with suet oil. Furthermore, these correspondence may elucidate the underlying mechanism of yang enhancement via kidney warming effects. Our study indicated that the mechanism of action mainly involved oxidative stress and amino acid metabolism. Here, we demonstrated the novel strategies of integrating metabolomics and network pharmacology in exploring of the mechanisms of traditional Chinese medicines.